Remotely delivered information, training and support for informal caregivers of people with dementia - González-Fraile, Eduardo; Ballesteros, Javier; Rueda, Jose R.; Santos-Zorrozua, Borja; Solà, Ivan; McCleery, Jenny (Cochrane database of systematic reviews, 2021)
Many people with dementia are cared for at home by unpaid informal caregivers, usually family members. Caregivers may experience a range of physical, emotional, financial and social harms, which are often described collectively as caregiver burden. The degree of burden experienced is associated with characteristics of the caregiver, such as gender, and characteristics of the person with dementia, such as dementia stage, and the presence of behavioural problems or neuropsychiatric disturbances. It is a strong predictor of admission to residential care for people with dementia. Psychoeducational interventions might prevent or reduce caregiver burden. Overall, they are intended to improve caregivers' knowledge about the disease and its care; to increase caregivers' sense of competence and their ability to cope with difficult situations; to relieve feelings of isolation and allow caregivers to attend to their own emotional and physical needs. These interventions are heterogeneous, varying in their theoretical framework, components, and delivery formats. Interventions that are delivered remotely, using printed materials, telephone or video technologies, may be particularly suitable for caregivers who have difficulty accessing face-to-face services because of their own health problems, poor access to transport, or absence of substitute care. During the COVID-19 pandemic, containment measures in many countries required people to be isolated in their homes, including people with dementia and their family carers. In such circumstances, there is no alternative to remote delivery of interventions. Objectives: To assess the efficacy and acceptability of remotely delivered interventions aiming to reduce burden and improve mood and quality of life of informal caregivers of people with dementia. Search methods: We searched the Specialised Register of the Cochrane Dementia and Cognitive Improvement Group, MEDLINE, Embase and four other databases, as well as two international trials registries, on 10 April 2020. We also examined the bibliographies of relevant review papers and published trials. Selection criteria: We included only randomised controlled trials that assessed the remote delivery of structured interventions for informal caregivers who were providing care for people with dementia living at home. Caregivers had to be unpaid adults (relatives or members of the person's community). The interventions could be delivered using printed materials, the telephone, the Internet or a mixture of these, but could not involve any face-to-face contact with professionals. We categorised intervention components as information, training or support. Information interventions included two key elements: (i) they provided standardised information, and (ii) the caregiver played a passive role. Support interventions promoted interaction with other people (professionals or peers). Training interventions trained caregivers in practical skills to manage care. We excluded interventions that were primarily individual psychotherapy. Our primary outcomes were caregiver burden, mood, health-related quality of life and dropout for any reason. Secondary outcomes were caregiver knowledge and skills, use of health and social care resources, admission of the person with dementia to institutional care, and quality of life of the person with dementia. Data collection and analysis: Study selection, data extraction and assessment of the risk of bias in included studies were done independently by two review authors. We used the Template for Intervention Description and Replication (TIDieR) to describe the interventions. We conducted meta-analyses using a random-effects model to derive estimates of effect size. We used GRADE methods to describe our degree of certainty about effect estimates. Main results: We included 26 studies in this review (2367 participants). We compared (1) interventions involving training, support or both, with or without information (experimental interventions) with usual treatment, waiting list or attention control (12 studies, 944 participants); and (2) the same experimental interventions with provision of information alone (14 studies, 1423 participants). We downgraded evidence for study limitations and, for some outcomes, for inconsistency between studies. There was a frequent risk of bias from self-rating of subjective outcomes by participants who were not blind to the intervention. Randomisation methods were not always well-reported and there was potential for attrition bias in some studies. Therefore, all evidence was of moderate or low certainty. In the comparison of experimental interventions with usual treatment, waiting list or attention control, we found that the experimental interventions probably have little or no effect on caregiver burden (nine studies, 597 participants; standardised mean difference (SMD) -0.06, 95% confidence interval (CI) -0.35 to 0.23); depressive symptoms (eight studies, 638 participants; SMD -0.05, 95% CI -0.22 to 0.12); or health-related quality of life (two studies, 311 participants; SMD 0.10, 95% CI -0.13 to 0.32). The experimental interventions probably result in little or no difference in dropout for any reason (eight studies, 661 participants; risk ratio (RR) 1.15, 95% CI 0.87 to 1.53). In the comparison of experimental interventions with a control condition of information alone, we found that experimental interventions may result in a slight reduction in caregiver burden (nine studies, 650 participants; SMD -0.24, 95% CI -0.51 to 0.04); probably result in a slight improvement in depressive symptoms (11 studies, 1100 participants; SMD -0.25, 95% CI -0.43 to -0.06); may result in little or no difference in caregiver health-related quality of life (two studies, 257 participants; SMD -0.03, 95% CI -0.28 to 0.21); and probably result in an increase in dropouts for any reason (12 studies, 1266 participants; RR 1.51, 95% CI 1.04 to 2.20). Authors' conclusions: Remotely delivered interventions including support, training or both, with or without information, may slightly reduce caregiver burden and improve caregiver depressive symptoms when compared with provision of information alone, but not when compared with usual treatment, waiting list or attention control. They seem to make little or no difference to health-related quality of life. Caregivers receiving training or support were more likely than those receiving information alone to drop out of the studies, which might limit applicability. The efficacy of these interventions may depend on the nature and availability of usual services in the study settings.
Keywords: affect; bias; caregiver burden; caregivers; dementia; family; health services accessibility; health services needs and demand; institutionalization; nursing homes; quality of life; randomized controlled trials as topic; Scopus; WOS(2)